2023
DOI: 10.1111/bjop.12641
|View full text |Cite
|
Sign up to set email alerts
|

Pain in the eye of the beholder: Variations in pain visual representations as a function of face ethnicity and culture

Abstract: Pain experienced by Black individuals is systematically underestimated, and recent studies have shown that part of this bias is rooted in perceptual factors. We used Reverse Correlation to estimate visual representations of the pain expression in Black and White faces, in participants originating from both Western and African countries. Groups of raters were then asked to evaluate the presence of pain and other emotions in these representations. A second group of White raters then evaluated those same represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The perception of pain varies across different cultures and individuals. Cultural factors have a relevant influence on how individuals experience and manage pain (Gingras et al, 2023). Studies have shown that pain experienced by Black individuals is systematically underestimated, and cultural factors may explain this phenomenon (Reis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The perception of pain varies across different cultures and individuals. Cultural factors have a relevant influence on how individuals experience and manage pain (Gingras et al, 2023). Studies have shown that pain experienced by Black individuals is systematically underestimated, and cultural factors may explain this phenomenon (Reis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%